The problem of dehydration in pediatrics - S.O. Kramarov; V.V. Yevtushenko; О.М. Yevtushenko; Ye.A. Maevska; V.V. Babak (Zdorovʹe Rebenka, 2021)
Dehydration syndrome often complicates the course of various diseases in children. The article covers the main pathological conditions that are accompanied by fluid loss, such as infectious diarrhea, cyclic vomiting syndrome, non-diabetic ketosis and ketoacidosis. The pathophysiological mechanisms that lead to water and electrolyte loss are described, as well as methods for correcting dehydration in pediatrics. We presented the results of a clinical study of Reogel, which was used for oral rehydration in children with acute infectious diarrhea receiving inpatient treatment. According to the results of this observation, we did not find a significant difference in the duration of the main clinical symptoms of the disease, such as diarrhea, vomiting and dehydration symptoms, as well as the frequency and duration of parenteral rehydration between groups of children receiving Reogel and standard oral rehydration. The results of this study give grounds to consider Reogel as an alternative to traditional oral rehydration in children with infectious diarrhea, accompanied by mild and moderate dehydration.